JURIDICAL ANALYSIS OF INVESTIGATION IN THE CASE OF FORGIVENESS OF VACCINE CERTIFICATES BY POLICE INVESTIGATORS POLRESTA BARELANG - Bayu Septa, Anjas; P. Siadari, Lagat; Parameshwara, Parameshwara (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The construction of the journal topic above is: "Juridical Analysis of Investigation of Vaccine Certificate Forgery Cases by Barelang Police Police Investigators", with the formulation of the problem: How are the Legal Arrangements, Implementation, Constraint Factors and Solutions to the Investigation of Vaccine Certificate Counterfeiting Cases by Barelang Police Police Investigators?. The type of writing is normative law, using legal research methodology, supported by secondary data, and using a qualitative approach, and to obtain secondary data, obtained through library research. For the grand theory, Jeremy uses the theory of happiness law (utilitarianism) by Jeremy Bentham, middle theory uses the legal theory of victimology and applied theory uses the theory of legal certainty. The results of the analysis concluded, (1) The application of material criminal law to the crime of counterfeiting in the jurisdiction of the Barelang Police is very good and very complete in accordance with the laws and regulations. (2) the perpetrators of the criminal act of counterfeiting at the Barelang Police have been treated in accordance with the procedures established by the applicable laws and regulations, but there are still obstacles that come from inside and outside the institution so that the number of cases of the crime of counterfeiting vaccine certificates is not also down.